Developing mathematics learning media based on e-learning using moodle on geometry subject to improve students' higher order thinking skills - Sumarwati, Sri; Fitriyani, Harina; Setiaji, Fathin Muhammad Azhar; Amiruddin, Mohd Hasril; Jalil, Siti Afiat (2019)
21st Century teaching and learning strategies related to the various methods used include the use of appropriate tools with the latest technological developments to help students to understand clearly about the content of the subject. Therefore, the need for the 21st Century teaching more focused on the development of students' higher-order thinking skills is increasingly urgent. This study aims to develop mathematics learning media based on e-learning using MOODLE (Modular Object-Oriented Dynamic Learning Environment) software on the geometry of the flat side subject to improve higher-order thinking skills among secondary school students. The analysis in this study is based on the ADDIE Instructional Model (Analysis, Design, Development, Implementation, Evaluation). The respondents in this study were three lecturers who are experts in the field of mathematics education, three teachers in the field of information technology and 70 secondary school students in Yogyakarta, Indonesia was selected using the purposive sampling method. The findings of this study have shown that mathematics learning media based on e-learning using MOODLE very suitable for encouraging students to use the mind to understand, interpret, analyze and manipulate information to find possible solutions for various problems, especially related to the geometry of the flat side subject. Besides, based on mathematics learning media based on e-learning using MOODLE able to encourage students to think, to generate new ideas, to focus and to be active throughout the teaching and learning activities. The results of this study are expected can be one of the teaching tools which can help in learning activities and a catalyst for the improvement of the quality of students' thinking.